Research Progress on Epigenetics of Diabetic Cardiomyopathy in Type 2 Diabetes - Deng, Jianxin; Liao, Yunxiu; Liu, Jianpin; Liu, Wenjuan; Yan, Dewen (Frontiers in Cell and Developmental Biology, 2021)
Diabetic cardiomyopathy (DCM) is characterized in its early stages by diastolic relaxation abnormalities and later by clinical heart failure in the absence of dyslipidemia, hypertension, and coronary artery disease. DCM contributes to high mortality and morbidity in diabetic populations and diabetes is a polygenic, heritable and a complex disease, and the environmental factor combined action. Recent studies have demonstrated that epigenetics directly or indirectly contributes to the pathogenesis of DCM. Although the role of epigenetic mechanisms (such as DNA methylation, histone modifications, and non-coding RNAs) have been recognized in the pathogenesis of DCM. However, its role in DCM remains largely unexplored. Better understanding of the research progress of epigenetics will provide a new measure to prevent and treat DCM.